Patients’ Perspectives on Digital Health Tools - Madanian, Samaneh; Nakarada-Kordic, Ivana; Reay, Stephen; Chetty, T'Heniel (Elsevier BV, 2023)
Objective Digital technology has changed the way healthcare is delivered and accessed. However, the focus is mostly on technology and clinical aspects. This review aimed to integrate and critically analyse the available knowledge regarding patients' perspectives on digital health tools and identify facilitators and barriers to their uptake. Methods A narrative review was conducted using the Scopus and Google Scholar databases. Information related to facilitators and barriers to uptake was synthesised and interpreted using thematic and content analyses, respectively. Results Seventy-one out of 1722 articles identified were eligible for inclusion. Patient empowerment, self-management, and personalisation were identified as the main factors that contributed to patient uptake in using digital health tools. Digital literacy, health literacy, and privacy concerns were identified as barriers to the uptake of digital health technology. Conclusion Digital health technologies have changed the way healthcare is experienced by patients. Research highlights the disconnect between the development and implementation of digital health tools and the patients they are created for. This review may serve as the foundation for future research incorporating patients' perspectives to help increase patients' engagement with emerging technologies.
Keywords: 4203 Health Services and Systems; 42 Health Sciences; Networking and Information Technology R&D (NITRD); 7 Management of diseases and conditions; 8 Health and social care services research; 7.1 Individual care needs; 8.1 Organisation and delivery of services; Generic health relevance; 3 Good Health and Well Being